2018
DOI: 10.3233/jad-180259
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepigenetics and Alzheimer’s Disease: An Update

Abstract: Epigenetics is the study of changes in gene expression which may be triggered by both genetic and environmental factors, and independent from changes to the underlying DNA sequence-a change in phenotype without a change in genotype-which in turn affects how cells read genes. Epigenetic changes represent a regular and natural occurrence but can be influenced also by factors such as age, environment, and disease state. Epigenetic modifications can manifest themselves not only as the manner in which cells termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 164 publications
0
17
0
Order By: Relevance
“…Many of these altered pathways are considered primary factors in age-related diseases, including cancer, neurodegenerative diseases, atherosclerosis, and inflammation. AD is associated with dysregulation of DNA methylation, histone modifications, and non-coding RNAs (De Jager et al, 2014; Zusso et al, 2018). Further, recent findings point to a role for 5hmC in the development of diseases, including AD, since global levels of 5mC and 5hmC are positively correlated with one another and with markers of AD, including amyloid beta, tau, and ubiquitin loads, potentially opening new pathways for AD treatment through correction of methylation and hydroxymethylation alterations (Coppieters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these altered pathways are considered primary factors in age-related diseases, including cancer, neurodegenerative diseases, atherosclerosis, and inflammation. AD is associated with dysregulation of DNA methylation, histone modifications, and non-coding RNAs (De Jager et al, 2014; Zusso et al, 2018). Further, recent findings point to a role for 5hmC in the development of diseases, including AD, since global levels of 5mC and 5hmC are positively correlated with one another and with markers of AD, including amyloid beta, tau, and ubiquitin loads, potentially opening new pathways for AD treatment through correction of methylation and hydroxymethylation alterations (Coppieters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This process takes place mainly in genomic regions abundant in CpG dinucleotides called CpG islands, which are found in both promoters and gene bodies. 4,9,10 DNA methylation in the promoter results in the outward projection of the bulky additional methyl group, leading to the spatial hindrance that prevents the binding of RNA polymerase. 11 These structural changes perturb the attachment of transcription factors to the transcription start site, suppressing gene transcription.…”
Section: Mechanism Of Dna Methylationmentioning
confidence: 99%
“…3 Indeed, collective studies in the field of neuroepigenetics have suggested an association between dysregulated epigenetic modifications and AD. 4 Among the epigenetic mechanisms, histone modifications are relatively more established in relation to their role in AD. Treatments based on histone deacetylase inhibition have shown promising progress in drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs are involved in cerebral inflammatory responses and amyloidogenic pathways. The altered production and metabolism of a few of miRNAs (miRNA-9, miRNA-34a, miRNA-125b, miRNA-146a and miRNA-155) may lead to AD-related aberrant molecular pathways including BACE1 hyperactivity, tau hyperphosphorylation, and neuroinflammation [24]. Blood cells may represent another privileged compartmental sources of peripheral indicators of neurodegeneration.…”
Section: Peripheral Exosomes and Micrornas As Novel Research Field Inmentioning
confidence: 99%